Politeness Phenomena in Rempung Language - Muhammad Hudri; Irwandi Irwandi (Linguistics and ELT Journal, 2020)
This study aims at identifying the social structures in Rempung Village, elaborating the reflection of social structure in politeness, elaborating the influence of social structure and politeness phenomena toward the lexical levels particularly at behavioral verbs. The data were gathered through observation and interview. The instruments used in doing observation were note taking and recording. Furthermore, the informants are the speakers of Rempung language who reside at RW.01 Derma Bhakti, Rempung.  The study found that there are only two social classes exist in Rempung, they are higher-class and lower-class persons. In addition, there are also two language levels in Rempung namely polite and ordinary forms. The social structures influence the use of language in Rempung. Tau jamaq/tau ba’ (the lower-class person) tend to use basa alis (polite form of language) when speaking to tau reaq/tau bo (the higher-class person). It is also used by tau reaq to speak to other tau reaq who have distant relation. On the contrary, tau reaq commonly uses basa jamaq (ordinary form) in speaking to tau jamaq. Basa jamaq is also used by tau jamaq to speak to other tau jamaq, and among tau reaq who have close relation.